2015
DOI: 10.3389/fimmu.2015.00269
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota and Immunity: Possible Role in Sudden Infant Death Syndrome

Abstract: The gut microbiome influences the development of the immune system of young mammals; the establishment of a normal gut microbiome is thought to be important for the health of the infant during its early development. As the role of bacteria in the causation of sudden infant death syndrome (SIDS) is backed by strong evidence, the balance between host immunity and potential bacterial pathogens is likely to be pivotal. Bacterial colonization of the infant colon is influenced by age, mode of delivery, diet, environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 94 publications
(117 reference statements)
1
10
0
Order By: Relevance
“…If certain E. coli can cause ARDS, then it is possible that a similar mechanism occurs in SIDS given that the clinical and pathological findings in SIDS babies reflect a process consistent with sepsis and/or toxemic shock. This is supported by sterile site evidence of bacteremia ( 33 , 44 , 45 ) and the knowledge that bacteremia is a profound inducer of hypoxemia (thought to be involved in the final pathway). This model is supported by clinical evidence of fever [sweat-soaked bedding ( 46 ) and raised rectal temperature ( 47 ) and the pathological findings of intrathoracic petechiae, heavy wet lungs, and liquid heart blood and elevated fibrin degradation products ( 48 , 49 )], findings compatible with a process of bacterial sepsis.…”
Section: Escherichia Coli and Sidsmentioning
confidence: 86%
See 1 more Smart Citation
“…If certain E. coli can cause ARDS, then it is possible that a similar mechanism occurs in SIDS given that the clinical and pathological findings in SIDS babies reflect a process consistent with sepsis and/or toxemic shock. This is supported by sterile site evidence of bacteremia ( 33 , 44 , 45 ) and the knowledge that bacteremia is a profound inducer of hypoxemia (thought to be involved in the final pathway). This model is supported by clinical evidence of fever [sweat-soaked bedding ( 46 ) and raised rectal temperature ( 47 ) and the pathological findings of intrathoracic petechiae, heavy wet lungs, and liquid heart blood and elevated fibrin degradation products ( 48 , 49 )], findings compatible with a process of bacterial sepsis.…”
Section: Escherichia Coli and Sidsmentioning
confidence: 86%
“…α-hemolysin-producing E. coli needs to be considered in SIDS. The effects of HLyA and/or Ehly on the enterocyte and gut wall integrity could result in mucosal perturbation or damage promoting translocation of bacteria ( E. coli or other gut microbiota) into the bloodstream either through induced inflammation or directly [see below and the accompanying article by Goldwater ( 33 )].…”
Section: Escherichia Coli and Sidsmentioning
confidence: 99%
“…The recent arrival of comprehensive analytical procedures such as 16S rRNA gene sequencing and next-generation sequencing has enabled wide-ranging analyses of species to be performed, and has accelerated the studies of gut microbiota. These revealed that the dysbiosis of gut microbiota is related to the development of various diseases not only during childhood but throughout life, including gastrointestinal diseases such as inflammatory intestinal disorder [3], irritable bowel syndrome [4], and necrotizing enterocolitis [5], as well as allergic diseases [6], obesity or metabolic syndrome [7], diabetes [8], autistic spectrum disorder [9], and sudden infant death syndrome [10].…”
Section: Effect Of Delivery Mode and Nutrition On Gut Microbiota In Nmentioning
confidence: 99%
“…Such a mechanism could operate in SIDS wherein an inflamed gut mucosa could promote microbial translocation into the bloodstream and cause overwhelming sepsis. 74 New information showing an otherwise previously unknown microbiome of the airways and lungs could also involve predisposition to abnormal inflammatory responses. 75 …”
Section: The Microbiome and Sidsmentioning
confidence: 99%